Effect of Season on Hematologic, Biochemical, and Hormonal Analytes in Rams of Two Breeds - Oikonomidis Ioannis L. (Sciendo, 2019)
Clinicopathological investigations are essential for the evaluation of the health status of ruminants. Apart from species-specific reference intervals, the effect of common biological factors should be considered for an accurate interpretation of laboratory data. The aim of this study was to evaluate the effect of season on hematologic and biochemical analytes, and serum total thyroxine and cortisol in adult rams of two breeds. Four blood samples (one every season) were collected from each ram. Complete blood count was performed on the Advia 120 (Siemens Healthcare Diagnostics, USA), while the differential leukocyte count was manually conducted. Biochemical and hormonal analyses were performed on Flexor E (Vital Scientific, The Netherlands), AVL 9180 (Roche Diagnostics, Belgium), and Immulite 1000 (Siemens Healthcare Diagnostics, USA), respectively. Linear mixed effects models (R language) were employed for statistical analyses. Forty-three (26 Chios, 17 Florina), adult, clinically healthy rams were included. Statistically significant (p<0.05), mostly breed-independent seasonal differences were observed in almost all of the analytes. However, when assessing these differences in view of the respective reference intervals, only a few of them were considered biologically important. Specifically, mild hyperglycemia and mild decrease in the concentration of total calcium and inorganic phosphorus were detected in winter, while a mild increase in thyroxine concentration (autumn) and creatine kinase activity (spring and summer) was also noted. In conclusion, seasonal effects should be considered when evaluating laboratory results in rams; however, season does not appear to have an essential effect on the clinicopathological profile of rams reared in the Mediterranean region.